Glutaminase and MMP-9 Downregulation in Cortex and Hippocampus of LPA1 Receptor Null Mice Correlate with Altered Dendritic Spine Plasticity - Peñalver Alonso, Ana; Campos-Sandoval, José Ángel; Blanco-Calvo, Eduardo; Cardona Ramírez, Carolina; Castilla, Laura; Martín-Rufián, Mercedes; Estivill-Torrús, Guillermo; Sánchez-Varo, Raquel María; Alonso-Carrión, Francisco José; Pérez-Hernández, Mercedes; Colado, María Isabel; Gutiérrez-Pérez, Antonia; et al. (Frontiers, 2017)
Lysophosphatidic acid (LPA) is an extracellular lipid mediator that regulates nervous system development and functions acting through G protein-coupled receptors (GPCRs). Here we explore the crosstalk between LPA1 receptor and glutamatergic transmission by examining expression of glutaminase (GA) isoforms in different brain areas isolated from wild-type (WT) and KOLPA1 mice. Silencing of LPA1 receptor induced a severe down-regulation of Gls-encoded long glutaminase protein variant (KGA) (glutaminase gene encoding the kidney-type isoforms, GLS) protein expression in several brain regions, particularly in brain cortex and hippocampus. Immunohistochemical assessment of protein levels for the second type of glutaminase (GA) isoform, glutaminase gene encoding the liver-type isoforms (GLS2), did not detect substantial differences with regard to WT animals. The regional mRNA levels of GLS were determined by real time RT-PCR and did not show significant variations, except for prefrontal and motor cortex values which clearly diminished in KO mice. Remarkably, Golgi staining of hippocampal regions showed an altered morphology of glutamatergic pyramidal cells dendritic spines towards a less mature filopodia-like phenotype, as compared with WT littermates. This structural change correlated with a strong decrease of active matrix-metalloproteinase (MMP) 9 in cerebral cortex and hippocampus of KOLPA1 mice. Taken together, these results demonstrate that LPA signaling through LPA1 influence expression of the main isoenzyme of glutamate biosynthesis with strong repercussions on dendritic spines maturation, which may partially explain the cognitive and learning defects previously reported for this colony of KOLPA1 mice.
Keywords: Isoenzimas; Neuroglia - Metabolismo; Glutaminase; Brain; Lysophosphatidic acid receptor; Dendritic spines